2019
DOI: 10.5194/amt-2019-23
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humidity effects on the detection of soluble and insoluble nanoparticles in butanol operated condensation particle counters

Abstract: Abstract. In this study the impact of humidity on heterogeneous nucleation of n-butanol onto hygroscopic and nonabsorbent particles was investigated using a fast expansion chamber and commercial continuous flow type condensation particle counters (CPCs). More specifically, we measured the activation probability of sodium chloride (NaCl) and silver (Ag) nano-particles by using n-butanol as condensing liquid with the size analyzing nuclei counter (SANC). In addition, the cut-off diameter of regular butanol based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In the third and fourth channels, two TSI UCPC Model 3776 with an inlet flow rate of 1.5 L/min were implemented and operated at modified temperature settings, i.e. the saturator temperature was set to 30.1°C and the condenser temperature set at 0.1°C for enhanced 120 particle activation (Barmpounis et al, 2018;Tauber et al, 2019). A water-based TSI CPC Model 3788 was employed in the https://doi.org/10.5194/acp-2019-1123 Preprint.…”
Section: The Dma-train Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third and fourth channels, two TSI UCPC Model 3776 with an inlet flow rate of 1.5 L/min were implemented and operated at modified temperature settings, i.e. the saturator temperature was set to 30.1°C and the condenser temperature set at 0.1°C for enhanced 120 particle activation (Barmpounis et al, 2018;Tauber et al, 2019). A water-based TSI CPC Model 3788 was employed in the https://doi.org/10.5194/acp-2019-1123 Preprint.…”
Section: The Dma-train Experimental Setupmentioning
confidence: 99%
“…Previous studies have shown that the RH and the seed solubility with respect to the working fluid have an influence on the CPC detection efficiency (Kangasluoma et al, 2013;Tauber et al, 2019). To appropriately account for the seed variability present in the atmosphere, we used the mean counting efficiency at the classified diameter using results of the counting efficiency for silver and sodium chloride particles exposed to 0% or 10% RH as a best estimate.…”
Section: Dma-train Data Considerationsmentioning
confidence: 99%